2011
DOI: 10.1007/s00167-011-1681-z
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral and tibiofemoral articular cartilage and subchondral bone health following arthroscopic partial medial meniscectomy

Abstract: Methods: For this cross-sectional study, 158 patients aged 30-55 years, without evidence of knee osteoarthritis at arthroscopic partial medial meniscectomy (APMM), and 38 controls were recruited. MRI was performed once on the operated knee for each subcohort of 3 months, 2 years, or 4 years post-surgery, and the randomly assigned knee of the controls. Cartilage volume, cartilage defects, and bone size were assessed using validated methods. Conclusions: Partial medial meniscectomy is associated with adverse eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…The effects of meniscal tears on knee stability and the development of osteoarthritis are now well documented, [11][12][13] as are the effects of instability on the meniscus. 7,14,15 However, the consequences of specific lesions of the meniscal roots and ligamentous attachments, and the complex relationships between instability, the meniscus, and tibial slope, are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of meniscal tears on knee stability and the development of osteoarthritis are now well documented, [11][12][13] as are the effects of instability on the meniscus. 7,14,15 However, the consequences of specific lesions of the meniscal roots and ligamentous attachments, and the complex relationships between instability, the meniscus, and tibial slope, are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Age may not play a crucial role in mediating this association as total tibial bone area was significantly associated with injury in both cohorts, although the effect size was consistently larger in the older cohort possibly reflecting the increased time since the injury. Several studies have examined the association between cartilage defects/loss and history of knee surgery [35]; however, there is limited data showing the same association with knee injury. Elsaid et al have shown in a rabbit injury model that knee injury can result in loss of boundary-lubricating ability of synovial fluid which can cause damage to the articular cartilage matrix [36].…”
Section: Discussionmentioning
confidence: 99%
“…People following APM are at increased risk of developing knee osteoarthritis in both the tibiofemoral and patellofemoral compartments (Englund and Lohmander, 2005;Wang et al, 2012). Although knee osteoarthritis is considered in part a mechanical disease (Felson, 2013), the pathogenesis of this debilitating condition is not well understood in patients following APM.…”
Section: Introductionmentioning
confidence: 99%